Pengaruh Edukasi Terhadap Tingkat Pengetahuan Anak Tentang Pencegahan Diare Di Sekolah Dasar Swasta Pelangi Medan - Intan Christie Gulo; Harsudianto Silaen (PT. Hasba Edukasi Mandiri, 2025)
Diarrhea is an endemic disease in Indonesia. Apart from that, diarrhea also has the potential to become an extraordinary event (KLB), which means that there is a possibility of a significant increase in the number of diarrhea cases in a certain time and area. Outbreaks of diarrhea can often be accompanied by death, especially if not treated quickly and appropriately. Therefore, it is important for society and the government to increase awareness about preventing and treating diarrhea. Objective: to determine the level of children's knowledge regarding preventing diarrhea. Method: quantitative research method with pre-experimental design and using the one group pretest – posttest design method. The sampling technique uses total sampling. Results: The results of this study show that there is an influence of diarrhea prevention education on the level of children's knowledge at SDS Pelangi Medan with a value of p value .000 or p < 0.005. Conclusion: there is a significant influence between diarrhea prevention education on children's knowledge level. Schools are expected to provide facilities and infrastructure to support the health of the school environment and school community. Suggestion: It is recommended that future researchers involve a larger and more diverse sample size and consider the perspectives of teachers and parents.